Penguatan Konsep Empati Sebagai Kepribadian Konselor Dalam Pandangan Islam: Strengthening the Concept of Empathy as a Counselor Personality in Islamic Views - Nurul Fitrian Eko Saputro; Nurjannah (UIN Kiai Haji Achmad Siddiq Jember, 2023)
This paper wants to know more about the concept of empathy that becomes the personality of the counselor according to the Islamic view. Using qualitative research methods with a literature study approach, search for related themes. The result of this study is that the personality of the counselor is a value and skill that must be possessed by a counselor. Empathy is one of the personality of counselors who not only comes from western theory but is also strengthened by the existence of Islamic values that further add to the completeness of concepts in carrying out effective counseling services.